Analysis of Potential Economic Value of Catfish Cultivation Waste as Liquid Organic Fertilizer in Benteng Somba Opu Village, Barombong District, Gowa Regency - Salman; Aris Baso; Benny Audy Jaya Gosari; Amiluddin; Sri Suro Adhawati; Kasri (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
This study aims to determine the amount of macronutrient content of nitrogen, phosphate and potassium from catfish culture waste as liquid organic fertilizer (POC) through a fermentation process at different times. As well as knowing the potential economic value, by determining the cost of production and the selling price of catfish farming waste products as liquid organic fertilizer in Benteng Somba Opu Village, Barombong District, Gowa Regency. This research was carried out for three months, from February to April 2021. The fermentation process used a simple experimental research design method, while the potential economic value used a quantitative descriptive research method. The results of the study on catfish culture wastewater contained N, P and K. Macro nutrient levels of catfish manure containing N (nitrogen) ranged from 0.98 - 1.67%, P (phosphorus) 1.89 - 3.40 % and K (potassium) 0.10-1.03%. Apart from the content of macro-nutrient levels to improve macro-nutrients in the soil, POC also provides additional income for catfish cultivators. HPP based on research results is Rp. 19,000 / liter. Comparison of the price of poc in the market with liquid organic fertilizer that has been fermented by comparing 3 brands of poc on the market with the same size, namely 1 liter. The average profit potential of liquid organic fertilizer from catfish farming waste in a month (30 days) is Rp. 884,190, / Month, where the desired POC selling price ranges from Rp.47,500-Rp.52,000,-. Although the potential is small, it is quite interesting for catfish cultivators to try. This is in line with the increase in the production process of catfish cultivation, so additional income in the production of liquid organic fertilizer will also increase.